Contrasts in the large herbivore faunas of the southern continents in the late Pleistocene and the ecological implications for human origins. (14th March 2013) - Owen‐Smith, Norman; Riddle, Brett
Abstract Aim Africa is renowned for the current abundance and diversity of its large mammals. The aim of this study was to assess distinctions evident in the functional composition of continental large herbivore faunas during the late Pleistocene before extinctions depleted the megafauna outside Africa. Location The African large herbivore fauna was compared with that formerly inhabiting South America, Australia, North America, Eurasia and tropical Asia during the late Pleistocene. Methods Pleistocene faunas were reconstructed from the literature in terms of their relative body size composition, grazer/browser contributions and taxonomic representations, omitting forest and island species. Results Although the three southern continents were closely similar in the overall species richness of large herbivores that they supported during the late Pleistocene, South America had a predominance of very large herbivores, while most of Australia's mammalian herbivores were relatively small and those of Africa were intermediate. Africa had many more grazers, especially in the size range 100–1000 kg, than other continents. The South American pattern resembled that in North America and Eurasia, while Africa and Australia diverged in different ways. Main conclusions Neither the total extent of savannas in each continent nor the morphological features enabling bovid radiation seemed adequate on their own to explain the greater richness of macrograzers in Africa. Africa is characterized by the widespread occurrence of arid/eutrophic savannas, which are unrepresented in other continents. The prevalence of savanna is partly attributable to the high elevation of interior eastern and southern Africa, associated with relatively low rainfall, and to the comparatively high soil fertility, related to volcanic influences. This promoted an abundance and diversity of medium‐sized grazing ruminants unrivalled elsewhere. Indigenous grasses in South America and Australia are less well adapted to withstand severe grazing than the African grasses introduced to support livestock. The locally high abundance of African ungulates presented conditions that facilitated the adaptive transition by early hominins from plant‐gatherers to meat‐scavengers.